Peran Kepuasan Kerja dalam Membentuk Loyalitas Karyawan melalui Keseimbangan Kehidupan Kerja dan Keterikatan Karyawan pada UPT PLN Malang - Lidia Andiani; Agussalim Andriansyah (Universitas Muhammadiyah Pontianak, 2026)
This study examines the role of job satisfaction as a mediator between work-life balance (WLB) and employee engagement on employee loyalty at UPT PLN Malang, using a sample of 85 respondents with SEM-PLS analysis. The study results show that WLB significantly and positively influences job satisfaction (coefficient 0.301; p-value 0.000), which then has a positive impact on employee loyalty (coefficient 0.359; p-value 0.002). However, the direct effect of WLB on employee loyalty is not significant (coefficient 0.043; p-value 0.332). Meanwhile, employee engagement has a strong and significant direct influence on job satisfaction (coefficient 0.624; p-value 0.000) and employee loyalty (coefficient 0.530; p-value 0.000). A key finding is that job satisfaction effectively mediates the impact of WLB and employee engagement on loyalty. This means that good WLB and high engagement increase job satisfaction, which ultimately becomes a key driver of employee loyalty. This study emphasizes the importance of job satisfaction as a strategic bridge to foster employee loyalty within an organization.